PERBANDINGAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN DARING DAN LURING MASA PANDEMI COVID-19 - Ika Juwita; Nanang Heriyana; Djon Lasmono (Universitas Tanjungpura, 2022)
This research aims to identify how to compare student learning motivation in online and offline learning during the Covid-19 pandemic in class XI at SMK PGRI Pontianak. This research formed a quantitative description by using descriptive method. The data collection technique was indirect communication with the data collection tool, a questionnaire, observation sheets, documentary studies, and data archives. Based on the results of research on Student Learning Motivation in Online and Offline Learning During the Covid-19 Pandemic in Class XI SMK PGRI Pontianak it can be said that it is going well: 1) Student motivation during online learning during the Covid-19 pandemic in class XI SMK PGRI Pontianak, the results of the motivation student learning using online learning has good results with a frequency of 1 student, the sufficient category with a frequency of 11 students, and the less category with a frequency of 3 students. 2) Student learning motivation during offline learning during the covid-19 pandemic in class XI SMK PGRI Pontianak, The results of student learning motivation using offline learning are good with a frequency of 3 students, the sufficient category with a frequency of 10 students, and the less category with a frequency of 2 students .3) Differences in student learning motivation in online and offline learning during the Covid-19 pandemic in class XI SMK PGRI Pontianak, from the calculation of the t test, it can be concluded that there are significant differences in student learning outcomes using online learning and offline learning in XI PGRI Vocational High School.